Effect of Corruption on Corporate Governance in Selected Area Offices of Deposit Money Banks in Enugu State, Nigeria - Emmanuel, K. Agbaeze; Chukwuma, Isaac Onyeyirichukwu; Ann, Ogbo; Agu, Agu Okoro (International Research Journal of Management, IT & Social Sciences, 2017)
The study seeks to examine the effect of corruption on corporate governance in selected area offices of deposit money banks in Enugu State, Nigeria. The specific objectives were to; (i) determine the extent to which bribery affects the board of directorsâ functions, (ii) ascertain the extent to which fraud affects the managersâ accountability, and (iii) identify the nature of the relationship existing between money laundering and shareholdersâ investment in selected area offices of deposit money banks in Enugu State, Nigeria. The study adopted the descriptive survey design. The population of the study was 1197, which comprised the senior and junior staff members of the five selected banks (United Bank for Africa Plc, First Bank of Nigeria Plc, Access Bank Plc, Fidelity Bank Plc, and Skye Bank Plc.). The sample size of 316 was obtained from the population using Freud and Williamâs formula at 5% error tolerance and 95% level of confidence. Data collection was done via questionnaire and oral interview guide. Simple Linear Regression Analysis and Pearson Product Moment Correlation were used for data analysis.